Konsep An-Nafs Menurut Tafsir Ibnu Katshir dan Tafsir Ilmi - Arifinsyah; Sari, Parima; Ismahani, Siti (Ikatan Da'i Indonesia, 2023)
The human soul has two sides, good and bad. It is very important and urgent to pay attention to. A noble soul, is not pleased with anything, except for something that has the highest, noblest and most commendable (best) end result. As for the lowly soul, he only revolves around lowly matters, he approaches these lowly matters as a fly lands on dirt. A noble and high soul will not be pleased with acts of tyranny, vulgarity, theft and betrayal, because his soul is bigger and more noble than all of that. Meanwhile, a lowly and lowly soul is the opposite. Then every soul will tend to something that is in harmony and in accordance with it. Nafs in the context of talking about humans refers to the side in humans that has the potential to be good or bad. Research on human nature at least contains human traits that are naturally inherent in humans, or laws that apply to the human psyche, in this case the concept of nafs in the Koran is very important. The importance of research on the nafs is not only limited to needs, but also to the interests of parsing, predicting and controlling human behavior, both individually and as a group, both in relation to the field of da'wah or education as well as the interests of society in national development.